Characterization of arm-gun movement during air pistol aiming phase - Pellegrini, B.; Schena, F. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Air pistol shooting is a sport requiring extreme movement precision. The purpose of our study is to collect and analyze kinematic data of arm/gun complex during the pointing phase in order to characterize movement and between segment coordination by means of time and frequency domain analysis techniques. Methods: Thirteen air pistol athletes participated to the recording sessions held at the 10 m shooting range. Kinematic data of neck, shoulder, elbow, wrist and gun were collected during the aiming phase using an optoelectronic motion capture system. Displacement series were split up in slow drift and tremor components. Amplitude of the movement of each segment and strength of the relationship between adjacent segments were estimated in time domain respectively by means of standard deviation and coefficient of regression. Moreover, coherence and phase spectral functions were calculated to assess between-segment coupling at different frequencies. Results: Significantly larger movements were seen for slow drift component with respect to tremor one for all segments especially for lateral movements. Higher between segment correlation were found for lateral direction and for slow drift component. The coherence calculated on vertical series of tremor component showed significant coupling at 1.5 Hz and 5-7 Hz with phase opposition between wrist and gun motion at 5-7 Hz. Conclusion: Slow drift motion appears to affect mainly lateral movements and all the segments were equally involved indicating a probable origin in postural body sway. Vertical displacements could be referred to shoulder and wrist motion with features typical of physiological tremor. Quantitative characterization of segments displacements during aiming phase may serve as a basis for scientific evaluation and training in competitive precision shooting.